The Effectiveness of Islamic Value Based Nursing Education in Controlling Hypertension Elderly at the Antara Community Health Center in Makassar City - Andani, Nur; Mulat, Trimaya Cahya; Khumaidi, Khumaidi (Jurnal Kesehatan Pasak Bumi Kalimantan, 2026)
Hypertension is one of the major health problems among the elderly, contributing to increased morbidity and mortality, thus requiring a comprehensive approach including the integration of spiritual values into nursing care. This study aimed to analyze the effectiveness of Islamic value-based nursing education in controlling blood pressure among elderly patients at the Antara Community Health Center in Makassar City. The research employed a quasi-experimental design with a pretest-posttest control group approach, involving elderly individuals diagnosed with hypertension selected through purposive sampling. The intervention consisted of Islamic value-based nursing education, including strengthening religious practices, spiritual stress management, and education on healthy lifestyles in accordance with Islamic teachings, delivered over a certain period. The results showed a significant reduction in systolic and diastolic blood pressure, as well as improved medication adherence and healthy lifestyle behaviors in the intervention group compared to the control group (p<0.05). In conclusion, Islamic value-based nursing education is effective in helping control hypertension among the elderly and can be recommended as an innovative approach in community nursing practice at primary healthcare services.Keywords:  Hypertension, Elderly, Nursing Education, Islamic Values, Community Nursing, Blood Pressure Control